Dechema chemistry data series : vapor - liquid equilibrium data collection 7 aromatic hydrocarbons - Gmehling, J.; Onken, U.; Arlt, W. (Dechema Frankfurt, 1997)
part 7
this is a minor changes In 2nd ed
Keywords: vapor -- liquid equilibrium